BLOOD PRESSURE AND ARTERIAL STIFFNESS: EFFECTS OF CANAGLIFLOZIN VERSUS PERINDOPRIL IN DIABETIC PATIENTS WITH ESSENTIAL HYPERTENSION. (June 2018) - Ramirez, A.J.; Sanchez, M.; Sanchez, R.
Abstract : Objective: Introduction: Hypertension control is a priority target for the reduction of cardiovascular and renal risks. In type 2 Diabetes, the blood pressure (BP) reduction has an important impact in decreasing macro and microvascular complications. Sodium-glucose co-transporter-2 (SGLT2), a newly developed oral anti-diabetic drug family is able to inhibit SGLT2, decrease glucose plasma levels, BP and weight. Arterial stiffness is an established risk factor for cardiovascular events and mortality. Treatment of hypertension improves arterial stiffness and SGLT2 have shown to reduce blood pressure and ameliorates pulse wave velocity Aims: To evaluate, in patients with type 2 diabetes and hypertension, pretreated with amlodipine, the effects of Canagliflozin, compared with Perindopril, an ACEI, after 6 months treatment on central blood pressure and carotid-femoral pulse wave velocity (c-f PWV). Design and method: Thirty type 2 diabetic patients with hypertension, pre-treated with amlodipine 10 mg daily and metformin 750–2000 mg daily, were randomized and a third medication was added; either canagliflozin 300 mg daily (n = 15, 9 female, mean age: 63 ± 8 y) or perindopril 10 mg daily (n = 15, 5 females, mean age 59 ± 4 y), for 6 months. Ambulatory blood pressure monitoring (ABPM) with Mobil-O-Graph device was assessed at baseline, and after 3 and 6 months of treatment. In addition, in all individuals before and after 6 months of treatment, the c-f PWV was measured by tonometry. Results: Both treatments significantly reduced either the office or ABPM systolic, diastolic and central systolic blood pressures. Similarly, in both groups, c-f PWV was improved after 6 months of treatment. Canagliflozin plus amlodipine significantly reduced HbA1C (8.1 ± 0.5% to 7.0 ± 0.4%; p < 0.05) after 6 months of treatment. Perindopril plus amlodipine failed to change HbA1C. In the same way, only canagliflozin significantly reduced uric acid and 24hs urinary sodium after 6 months treatment. Other security laboratory parameters, including GOT, GPT, bilirubin failed to show any change.ry Conclusions: Canagliflozin reduced ambulatory BP and central BP in diabetics patients. In addition, arterial stiffness was improved in a similar way to perindopril. These two conditions might be important for the cardiovascular protection effects of SGLT2 inhibitors